Triple crown leadership : building excellent, ethical, and enduring organizations - Vanourek, Bob (McGraw-Hill, 2012)
Providing compelling leadership lessons from an array of enterprises; including Zappos; Google; eBay; Infosys; Xerox; Spotify; Mayo Clinic; KIPP; Ashoka; and more; this compelling book shows you how to achieve high performance; integrity; and sustainability. --